1979
DOI: 10.7589/0090-3558-15.2.335
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION OF NEWCASTLE DISEASE VIRUS FROM TEALS (Anas crecca) IN IRAN

Abstract: Eight of 30 teals (Anas crecca) died several days following capture and Newcastle Disease Virus (NDV) was isolated from all eight. Brains from the dead birds were homogenized and inoculated into chicken embryos. The allantoic fluid from the embryos were inoculated into 10 domestic chickens susceptible to NDV and 10 chickens immunized against NDV. Eight of 10 (80%) susceptible chickens died, while the immunized chickens remained healthy. Anti-NDV serum showed complete homology against NDV and the eight isolates. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…In Iran, APMV-1 has been isolated from different avian species and wild birds such as teals, Japanese quails and ostriches for a long time while most of them have been detected as virulent NDV (Bozorgmherifard & Keyvanfar, 1979;Momayez et al, 2007;Ghiamirad et al, 2010). Moreover, several serological studies in domestic chickens in villages of Iran have reported high prevalence of NDV infections up to 65%, 69%, and 62% in the north, central, and south provinces, respectively (Hassanzadeh & Bozorgmehrifard, 2004;Bouzari & Mousavi Morekani, 2006;Hadipour, 2009;Rezaeianzadeh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, APMV-1 has been isolated from different avian species and wild birds such as teals, Japanese quails and ostriches for a long time while most of them have been detected as virulent NDV (Bozorgmherifard & Keyvanfar, 1979;Momayez et al, 2007;Ghiamirad et al, 2010). Moreover, several serological studies in domestic chickens in villages of Iran have reported high prevalence of NDV infections up to 65%, 69%, and 62% in the north, central, and south provinces, respectively (Hassanzadeh & Bozorgmehrifard, 2004;Bouzari & Mousavi Morekani, 2006;Hadipour, 2009;Rezaeianzadeh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Chez les Anatidés sauvages, l'infection naturelle conduisant à une maladie clinique n'a été que rarement citée. Bozorgmehri-Fard et Keyvanfar (1979) ont constaté des morts rapides chez des sarcelles capturées (Anas crecca) à partir desquelles le virus APMV-1 avait été isolé. Après infection naturelle par l'APMV-1, Estudillo (1972) Chez des colverts adultes, les signes cliniques sont apparus 2 jours après l'inoculation expérimentale de la forme hautement virulente du virus MN, isolé à partir de poulets (Friend et Trainer 1972;Friend et Franson, 1999).…”
Section: Canards Oies Et Cygnesunclassified
“…The NDV has a ~15 kb RNA genome that codes for six viral proteins in the order 5 -NP-P-M-F-HN-L-3 [2].Phylogenetic analysis based on genome length and sequence of the F gene has revealed that NDV strains consist of two distinct classes (I and II) within a single serotype, with class I containing nine genotypes (1)(2)(3)(4)(5)(6)(7)(8)(9) and class II containing 15 genetic groups including 10 previously established (I-IX, and XI) and five N Hosseini H et al new genotypes (X, XII, XIII, XIV and XV) [3] .NDV strains have been classified into three major pathotypes: lentogenic (low virulent), mesogenic(intermediate virulent), or velogenic (highly virulent) on the basis of pathogenicity for chicken [4]. Conventionally, the pathogenicity of a newly identified NDV isolate or strain is assessed by methods including the intra-cerebral pathogenicity index (ICPI), the mean death time (MDT), and/or intravenous pathogenicity index (IVPI).…”
Section: Introductionmentioning
confidence: 99%
“…In low virulence strains there are sequences in the same region of112G/E-K/R-Q-G/E-R116 and followed by Leucine at position 117 [6]. Newcastle disease is endemic in Iran and we have many reports for incidence of velogneic ND in commercial farms in recent years [7,8]. Recetly, molecular analysis have been accepted as an effective alternative to the in vivo assay (i.e.…”
Section: Introductionmentioning
confidence: 99%